Agronomic management for sustainable Pearlmillet-wheat cropping system in sandy loam soils - Kumar, Pawan; Kumar, Manoj; Yadav, S.K.; Nanwal, R.K. (Annals of Agricultural Research, 2016)
The experiment was undertaken to study the effect of farm yard manure (FYM) and higher seed rate on pearlmillet-wheat cropping system at CCS Haryana Agricultural University, Hisar, India during 2009-10 and 2010-11. Incorporation of FYM @ 10 t ha-1 in pearlmillet resulted in increased grain yield, net return and nutrients uptake over recommended dose of fertilizer and package in both the crops. Incorporation of FYM @10 t ha-1 before sowing of pearlmillet and 30 per cent higher seed rate in both the crops had increased grain yield, net return and nutrients uptake of pearlmillet and wheat over both recommended fertilizer application alone or with 10 t FYM ha-1 before sowing of pearlmillet. Inclusion of cluster bean as inter crop in pearlmillet also gave higher returns over recommended dose of fertilizers and package alone.